Implementation of Youth Information and Counseling Centers Related to HIV/AIDS Prevention in a Junior High School in Bandung - Shifa Nadya Rahma; Insi Farisa Desy Arya; Rudi Wisaksana (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Adolescents are the population group most at risk of HIV infection due to low knowledge about HIV/AIDS. The National Population and Family Planning Board (Badan Kependudukan dan Keluarga Berencana Nasional, BKKBN) has developed the Youth Information and Counseling Center (Pusat Informasi dan Konseling Remaja, PIK-R) Program as a forum for information and counseling services, one of which is about Adolescent Reproductive Health (ARH) including HIV/AIDS. This study aimed to explore whether the implementation of the programs related to HIV/AIDS prevention in adolescents, specifically in junior high school in Bandung City.Methods: A qualitative descriptive study was carried out at a junior high school in Bandung in August 2018. This study used a purposive sampling technique and data were collected by conducting in-depth interviews with nine program administrators who were then transcribed and coded based on the PIK-R management guidelines using the NVIVO12 software, observing the program activities and documentations study which were then triangulated.Results: Several indicators in the growing stage had been implemented according to the guidelines, consisting of mastering ARH education materials including HIV/AIDS, conducting activities in the form of providing materials and peer counseling although without a secretariat room, and establishing networks and partnerships.Conclusion: The PIK-R program can be a media for preventing HIV/AIDS among junior high school students in Bandung regardless of resource limitations. Therefore, supports from BKKBN and the school itself is needed to improve the implementation of this program.